Depressive symptoms and body mass index: co-morbidity and direction of association in a British birth cohort followed over 50 years. Issue 12 (September 2014) - Geoffroy, M.-C.; Li, L.; Power, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Background An unhealthy body mass index (BMI) has been associated with depression but the direction of association is uncertain. Our aim was to estimate the co-morbidity and direction of association between BMI and depressive symptoms at several ages, from childhood to mid-adulthood. Method The data were from 18 558 individuals born in 1 week in March 1958, in England, Scotland and Wales, with follow-up at ages 7, 11, 16, 23, 33, 42, 45 and 50 years. Depression (scores ⩾90th percentile) was identified from child/adolescent (teacher questionnaires) and adult (self-complete questionnaires and clinical interview) measures. BMI (kg/m2) measured in child/adolescence and adulthood was classified as underweight, normal, overweight or obese. Results In cross-sectional analyses, obesity and underweight (not overweight) from 11 to 45 years were associated respectively with 1.3–2.1 and 1.5–2.3 times the risk of depression compared with normal weight. Using the time-lagged generalized estimating equation (GEE) approach, we tested (a) whether underweight or obesity at prior ages (7 to 45 years) predicted subsequent risk of depression (11 to 50 years), adjusting for baseline depression; and (b) whether depression at prior ages (7 to 42 years) predicted subsequent risk of underweight or obesity (11 to 45 years), adjusting for baseline BMI. In longitudinal analyses, underweight predicted subsequent depression in both sexes [odds ratio (OR) 1.25, 95% confidence interval (CI) 1.11–1.40] and depression predicted subsequent underweight in males only (OR 1.84, 95% CI 1.52–2.23). Obesity predicted subsequent depressive symptoms in females only (OR 1.34, 95% CI 1.14–1.56), but depression did not predict obesity. Conclusions Clinicians should consider screening routinely for depression patients with unhealthy BMI, namely underweight and obesity, and vice versa.